Model of Similarity for the Conceptual Spaces Theory – Empirical Study - Gemel, Aleksander (Hybris, 2019)
This paper is devoted to the empirical evaluation of the extension of the Gärdenfors’ similarity model. His proposition insufficiently emphasizes the asymmetry of the modeled relationship of similarity. The proposed modification allows one to include the asymmetry of similarity and significantly sensitize the model to any contextual nuances. The model was compared with other theoretical proposals of geometrical modeling of similarity, including two asymmetric models and one symmetrical. The empirical evaluation of the model took place in two series of experiments. The obtained statistical data were compared with results inferred by tested models. The evaluation was based on iterative procedure designed to minimize the error generated by all compared models.